Molecular structures and vibrational frequencies for cis-[PdCl2(tmen)] and cis-[Pd(N-3)(2)(tmen)]: A DFT study - Treu-Filho, Oswaldo [UNESP]; Pinheiro, Jose C.; de Souza, Rodrigo A. [UNESP]; Kondo, Rogerio T.; de Paula Ferreira, Raimundo D.; de Figueiredo, Antonio F.; Mauro, Antonio Eduardo [UNESP] (Elsevier B.V., 2007)
Theoretical molecular structures of the complexes cis-[PdCl2(tmen)] and cis-[Pd(N-3)(2)(tmen)] (tmen = N,N,N',N'-tetramethylethylenediamine) were investigated using B3LYP/DFT method. The calculated molecular parameters, bond distances and angles, revealed a square-planar geometry around the metallic center for both compounds with the azide being linear. The theoretical infrared spectra of C, symmetry (electronic state (1)A) of the compounds are in agreement with the experimental data. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: palladium(II); N,N,N ',N '-tetramethylethylenediamine; infrared spectrum; molecular structure; DFT